Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMA Negeri 2 Kabanjahe - Johannes Gultom; Pargaulan Siagian (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Based on the analysis of needs in the learning process, it is necessary to develop interactive learning medium. This study aims to produce a product in the form of an interactive learning media based on Articulate Storyline which is valid, practical, and effective in improving students' understanding of mathematical concepts. This research and development is designed based on the stages of the ADDIE development model (Analyse, Design, Development, Implementation, and Evaluate). The subjects in this study were students of class X IPA 5 SMA Negeri 2 Kabanjahe, which consisted of 36 students. Based on the research which has been done, the validity of the interactive learning media developed obtained an average percentage of 87.26% by media experts and 87.82% by material experts with qualifications classified as very valid. Through the results of teacher responses and student responses in limited trials and field trials, an average percentage of assessment was obtained 94.5% by teachers, 85.67% by students in limited group trials and 86.07% by students in field trials with qualifications classified as very practical to be used in the learning process. The implementation of the application of interactive learning media that has been carried out to see the effectiveness with a set benchmark obtains results, namely for classical learning completeness, it reaches 80.56%, and the average percentage of effectiveness questionnaires is 94.72% with qualifications classified as effective. The increase in ability to understand mathematical concepts that occurs is a moderate increase. Based on the research acquisition data, it was concluded that the Articulate Storyline-based learning media developed in this study is valid, practical, and effective qualifications.